The molecular mechanism of the spontaneous substitution mutations caused by tautomerism of bases: Post Hartree-Fock study of the DNA rare base pairs - Danilov, V.I.; Hovorun, D.M.; Kurita, N. (Біополімери і клітина, 2005)
Gas-phase gradient optimization of the DNA rare base pairs containing lactam-lactim and amino-imino tautomers was carried oat using the Hartree-Fock (HF), Density Functional Theory (DFT) and the second-order Moller-Plesset perturbation (MP2) methods at the 6-31G(d, p) basis set. It is shown that full geometry optimization at the MP2 level leads to an intrinsically nonplanar propeller-twisted and buckled geometry of G*-T and G-T* base pairs. The nonplanarity of the pairs is caused by pyramidalization of the amino nitrogen atoms, which is underestimated by the HF and DFT methods. This justifies the importance of geometry optimization at the MP2 level for obtaining reliable prediction of the charge distribution, molecular dipole moments and geometrical structure of the base pairs. The comparison of the formation energies for the rare base pairs shows the energetical preference of the G*-T and A-C* base pairs as compared with the G-T* and A*-C ones, respectively. It is detected that the stabilization energies of the G-T* and A*-C base pairs describing the interaction between monomers are essentially larger than those of the G*-T and A-C* base pairs, respectively. An analysis of the decomposition members for molecular HF interaction energies by Morokuma-Kitaura (MK) and the Reduced Variational Space (RVS) methods showed that the nature of a larger stability of the G-T* and A*-C base pairs as compared to the G*-T and A-C* ones is due to the electrostatic interactions by 60–65 % and the polarization and charge transfer interactions by 35–40 %. Здійснено газофазну градієнтну оптимізацію рідкісних пар основ ДНК, які включають у себе лактам-лактимні і аміно-імінні таутомери, за допомогою методу Хартрі-Фока (ХФ), теорії функціонала густини (ТФГ) та другого порядку теорії збурень Моллера-Плессета (МП2) у базисі 6-31G(d, р). Показано, що повна оптимізація геометрії на рівні МП2 веде до внутрішньо неплоскої пропелер-обертальної і вигнутої геометрії пар основ G*-T і G-T*. Неплощинність пар обумовлена пірамідалізацією атомів азоту аміногрупи, яка недооцінюється методами ХФ і ТФГ. Це виправдовує важливість оптимізації геометрії на рівні МП2 для отримання помірко ваного передбачення розподілу зарядів, молекулярних дипольних моментів і геометричної структури пар основ. Порівняння енергій формування рідкісних пар основ демонструє енергетичну перевагу пар основ G*-T і А-С* стосовно пар G-T* і А*-С. Виявлено, що величини енергій стабілізації пар основ G-T* і А*-С, які описують взаємодію між мономерами, значно більші за аналогічні значення пар основ G*-T і А-С* відповідно. Використовуючи аналіз членів розкладання ХФ енергій молекулярної взаємодії методами Морокуми-Кітаури і зменшеного варіаційного простору, знайдено, що природа більшої стабільності пар основ G-T* і А*-С порівняно з парами G*-T і А-С* на 60–65 % обумовлена електростатичними взаємодіями і на 35–40 % — поляризаційними взаємодіями і взаємодіями з перенесенням заряду відповідно. Gas-phase gradient optimization of the DNA rare base pairs containing lactam-lactim and amino-imino tautomers was carried oat using the Hartree-Fock (HF), Density Functional Theory (DFT) and the second-order Moller-Plesset perturbation (MP2) methods at the 6-31G(d, p) basis set. It is shown that full geometry optimization at the MP2 level leads to an intrinsically nonplanar propeller-twisted and buckled geometry of G*-T and G-T* base pairs. The nonplanarity of the pairs is caused by pyramidalization of the amino nitrogen atoms, which is underestimated by the HF and DFT methods. This justifies the importance of geometry optimization at the MP2 level for obtaining reliable prediction of the charge distribution, molecular dipole moments and geometrical structure of the base pairs. The comparison of the formation energies for the rare base pairs shows the energetical preference of the G*-T and A-C* base pairs as compared with the G-T* and A*-C ones, respectively. It is detected that the stabilization energies of the G-T* and A*-C base pairs describing the interaction between monomers are essentially larger than those of the G*-T and A-C* base pairs, respectively. An analysis of the decomposition members for molecular HF interaction energies by Morokuma-Kitaura (MK) and the Reduced Variational Space (RVS) methods showed that the nature of a larger stability of the G-T* and A*-C base pairs as compared to the G*-T and A-C* ones is due to the electrostatic interactions by 60–65 % and the polarization and charge transfer interactions by 35–40 %.